A bibliometric analysis for global research trends on ectomycorrhizae over the past thirty years. Issue 4 (22nd October 2018) - Jiang, Xu; Yanbin, Liu
Abstract : Purpose: Based on the significance of ectomycorrhizae (ECM) and increased publication activity on this subject, it was decided to carry out a bibliometric analysis of scientific outputs in this area. The purpose of this study is to reveal the research trends of scientific outputs on ECM for the past 30 years and provide a potential guide for future research. Design/methodology/approach: A method of bibliometric analysis was performed, based on the online version of the Science Citation Index Expanded, Web of Science, from 1986 to 2017. The authors evaluated the publication types, languages, source countries, journals, the patterns of publication outputs, most-cited articles, most-productive authors, institutional distributions, subject categories, high-frequency keywords and keywords plus and high-frequency terms in the title and abstract of ectomycorrhizal research. Keywords, keywords plus and high-frequency terms in the title and abstract were analyzed via VOSviewer to illustrate the extent of co-occurrence. This study further describes the recent research priority or hotspots and reveals the research trends. Findings: From 1986 to 2017, the publication output on ECM showed a rising trend; the number of articles has rapidly increased after 2003. Based on co-occurrence analysis for keywords, keywords plus and terms in the title and abstract, "ectomycorrhizal fungi" is the most popular keyword and keywords plus; "concentration" is the most high-frequency terms in the title and abstracts. Plant biology, mycology and ecology are the hotspots in the ectomycorrhizal research. Ectomycorrhizal taxonomy, the molecular mechanisms of ectomycorrhizal symbioses and the common mycorrhizal networks are the future direction. Originality/value: A bibliometric analysis has been carried out to analyze the trends of ECM research with 30 years. This study provides a potential guide for future research related to ectomycorrhizae.